2010
DOI: 10.1016/j.ajic.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Electronic surveillance systems in infection prevention: Organizational support, program characteristics, and user satisfaction

Abstract: Background The use of electronic surveillance systems (ESSs) is gradually increasing in infection prevention and control programs. Little is known about the characteristics of hospitals that have a ESS, user satisfaction with ESSs, and organizational support for implementation of ESSs. Methods A total of 350 acute care hospitals in California were invited to participate in a Web-based survey; 207 hospitals (59%) agreed to participate. The survey included a description of infection prevention and control depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 21 publications
(26 reference statements)
0
25
0
1
Order By: Relevance
“…A 2008–2009 survey estimated that approximately one third of California hospitals used automated surveillance technology to monitor hospital-acquired infections (Halpin et al, 2011). Similarly, a survey of hospitals in the Northeastern United States found that one third of hospitals had an electronic surveillance system in place (Grota et al, 2010). Such systems were used to detect outbreaks, analyze data, and generate reports of hospital-acquired infections (Grota et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2008–2009 survey estimated that approximately one third of California hospitals used automated surveillance technology to monitor hospital-acquired infections (Halpin et al, 2011). Similarly, a survey of hospitals in the Northeastern United States found that one third of hospitals had an electronic surveillance system in place (Grota et al, 2010). Such systems were used to detect outbreaks, analyze data, and generate reports of hospital-acquired infections (Grota et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a survey of hospitals in the Northeastern United States found that one third of hospitals had an electronic surveillance system in place (Grota et al, 2010). Such systems were used to detect outbreaks, analyze data, and generate reports of hospital-acquired infections (Grota et al, 2010). As several states mandate reporting infection rates of MRSA and many more require some form of reporting of hospital-acquired infections (Committee to Reduce Infection Deaths, 2011), many hospitals may have data on the total number of cases in many outbreaks for several pathogens of concern.…”
Section: Discussionmentioning
confidence: 99%
“…In response, IPs have adopted electronically assisted surveillance technology to streamline surveillance responsibilities, with nearly one-fourth of organizations in California using such tools in a 2010 report. 1 Arguably, these surveillance tools emphasize the data collection and surveillance responsibilities of the IP but may have limited utility in actively preventing infections or directly impacting patient care.…”
mentioning
confidence: 99%
“…Information technology solutions (eg, electronic surveillance systems) are designed to support and enhance decision-making in infection control. 22 The role and scope of ICPs has been evolving, with surveillance activities accounting for a large proportion of the infection control workload. 10 The increasing availability and use of information technology solutions have the potential to decrease the time spent on conducting manual surveillance, thereby making infection control teams more efficient and potentially releasing capacity for other initiatives.…”
Section: Discussionmentioning
confidence: 99%